1996
DOI: 10.1080/03079459608419183
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between neutralizing antibody titre and protection from tenosynovitis in avian reovirus infections

Abstract: SUMMARYThe relationship between neutralizing antibody titre and protection from tenosynovitis caused by avian reovirus infection was examined using actively or passively immunized chickens. Actively immunized groups which developed geometric mean neutralizing antibody titres (GMT) of 1:238 or higher exhibited good protection (more than 71%) against challenge with avian reovirus strain 58-132 via the footpad. On the other hand, 87% of passively immunized chicks, which received chicken serum hyperimmune to avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The importance of neutralizing antibodies and their level in protection against tenosynovitis caused by ARV has been previously demonstrated (Takase et al, 1996). The protective ability of antibodies was found to be type specific, with marginal protection against strains of heterologous ARV serotypes (Meanger et al, 1997).…”
Section: Discussionmentioning
confidence: 83%
“…The importance of neutralizing antibodies and their level in protection against tenosynovitis caused by ARV has been previously demonstrated (Takase et al, 1996). The protective ability of antibodies was found to be type specific, with marginal protection against strains of heterologous ARV serotypes (Meanger et al, 1997).…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that there is an age-related resistance to tenosynovitis caused by avian reovirus infection (Jones & Georgiou, 1984), but that it is therefore important to protect chickens at an early age. Maternal antibodies in progeny from vaccinated breeder flocks offer this protection (Van der Heide et al, 1976;Eidson et al, 1979;Wood & Thornton, 1981;Jones & Nwajei, 1985, Takase et al, 1996aMeanger et al, 1997). Another way to achieve early protection is by vaccination with attenuated reovirus vaccines at 1 day of age.…”
Section: Discussionmentioning
confidence: 99%